Worldly consumers: the demand for maps in Renaissance Italy - Carlton, Genevieve (The University of Chicago Press, 2015)
Introduction: finding the consumers of sixteenth-century maps -- Capturing the world on paper: the visual tradition and mapmaking -- The commerce of cartography: printing, price, and Francesco Rosselli -- A buyer's market: map ownership in Venice and Florence, 1460-1630 -- A world unknown to the ancients: the demand for cartographic novelty -- The power of knowledge: education and curiosity in cartographic prints -- Making an impression: the display of maps in sixteenth-century Italian homes -- Conclusion: worldly consumers and the meaning of maps